Hepatitis C viral load in HCV-monoinfected and HCV/HIV-1-, HCV/HTLV-1/-2-, and HCV/HIV/HTLV-1/-2-co-infected patients from São Paulo, Brazil - Alves,Fabiana Aparecida (2018)
ABSTRACT Co-infections of hepatitis C virus (HCV) and either human immunodeficiency virus type 1 (HIV-1), human T-cell lymphotropic virus type 1 (HTLV-1) or type 2 (HTLV-2) have been described as having an impact on HCV viremia and subsequent disease progression. HCV load in serum samples from 622 patients (343 males, 279 females; median age 50.8 years) from São Paulo/southeast Brazil was analyzed using the Abbott Real Time HCV assay (Abbott Molecular Inc., IL, USA). Samples were obtained from HCV-monoinfected (n = 548), HCV/HIV-1- (n = 41), HCV/HTLV-1- (n = 16), HCV/HTLV-2- (n = 8), HCV/HIV/HTLV-1- (n = 4), and HCV/HIV/HTLV-2-co-infected (n = 5) patients, and results were compared among the groups and according to sex. The median HCV load in HCV-monoinfected patients was 5.23 log10 IU/mL and 0.31 log10 higher in men than in women. Increases in viral load of 0.51 log10, 0.54 log10, and 1.43 log10 IU/mL were detected in HCV/HIV-1-, HCV/HTLV-1- and HCV/HIV/HTLV-1-co-infected individuals, respectively, compared with HCV-monoinfected counterparts. In contrast, compared to HCV/HIV co-infected patients, HCV/HTLV-2-co-infected patients had an HCV load of 5.0 log10 IU/mL, whereas HCV/HIV/HTLV-2-co-infected patients had a median load 0.37 log10 IU/mL lower. Significant differences in HCV loads were detected, with males and HCV/HIV-1- and HCV/HIV/HTLV-1-co-infected patients presenting the highest values. Conversely, females and HCV/HTLV-2-co-infected patients exhibited lower HCV loads. Overall, HCV viremia is increased in HIV and/or HTLV-1-co-infection and decreased in HTLV-2 co-infection.